113 Influence of cattle stress response to restraint method on artificial insemination pregnancy rates. (29th July 2019) - Carrell, Russell C; Smith, William B; Kinman, Lea A; Mercadante, Vitor R G; Roper, David
Abstract: Activation of physiological stress responses have been associated with decreased pregnancy rates in beef cattle. Therefore, alternative cattle restraint methods have been developed to reduce this negative impact. However, little evidence exists comparing pregnancy outcomes of differing methods. Thus our objective was to determine if a difference was present in pregnancy rate to fixed-time artificial insemination in Bos taurus beef females when using a breeding box (b) versus a squeeze chute (c). Cows and heifers from two separate locations (Virginia Tech University, VT; and R.A. Brown Ranch, RAB) were exposed to FTAI protocols at location of origin while restrained in a squeeze chute (n = 169) or a breeding box (n = 162). Females were exposed to the 7 day Co-Sync + CIDR protocol pre-breeding. At day of breeding, females were randomly assigned to treatment. Immediately following breeding, blood was collected via coccygeal venipuncture for assessment of plasma cortisol concentration using an automated ELISA assay (Immulite 2000 XPi, Siemens). Chute and Exit Score (1–5) were assessed at the time of breeding by a trained technician at each location. Pregnancy was verified thirty days post-breeding via rectal ultrasonography. Pregnancy rate (PROC FREQ) and cortisol (PROC GLIMMIX) were analyzed using SAS version 9.4. Also, a Linear Regression Model (SAS version 9.4) was used to determine relationships between chute score, exit score, and cortisol. It was found that there was no difference in pregnancy rate between the breeding box and the squeeze chute (61.73% vs 64.71%, P = 0.31, respectively). Cortisol showed no difference between b and c (59.44±10.17 vs 58.61±10.16, P = 0.68, respectively). There was no linear relationship between cortisol, exit score, and chute score (P = 0.14). It can be concluded that stress responses are similar between the breeding box and squeeze chute. Therefore females will have similar pregnancy rates when exposed to FTAI in either restraint mechanism.